Enhanced Decolorization and Treatment of Textile Dye Wastewater Through Adsorption on Acid Modified Corncob Derived Biochar. Issue 39 (20th October 2020) - Sonu, Kumar; Sogani, Monika; Syed, Zainab; Dongre, Aman; Sharma, Gopesh
Abstract: Eco‐friendly biochar derived from the cost‐effective and easily accessible agricultural waste corncob has been utilized as an adsorbent for decolorization of real textile dye wastewater (RTDW). Slow pyrolysis of the corncob was done in a temperature range of 450–550 °C with a consistent heating rate to produce biochar. The biochar yield reduced with increasing temperature of pyrolysis. Chemical treatment of biochar (BC) with sulfuric acid was done to improve the adsorption efficiency. Batch studies were carried out for decolorization of RTDW by varying key reaction parameters in order to further optimize these ones. Significantly high decolorization efficiency of up to 98 % was obtained using acid modified biochar (MBC). The maximum adsorption of dyes with MBC was found to be 6.02 mg g −1 in 45 minutes at ambient temperature. Advance analytics including Fourier Transform Infrared Spectroscopy, Scanning Electron Microscopy and Zeta Potential etc. were carried out to characterize the adsorbents and to see the changes during the pyrolysis and adsorption processes. The kinetic studies demonstrated that Lagergren's pseudo‐II order model was the best fit for both BC and MBC. Also, MBC showed good recyclability as adsorbent when used two more times after degeneration. The germination % of Vigna radiata L . was studied to evaluate the toxicity of the effluents which depicted that dye wastewater after the adsorption by MBC was safe for agricultural use. Abstract : Real textile dye wastewater (RTDW) treatment and decolorization through adsorption on eco‐friendly and cost‐effective biochar produced from an easily available agricultural waste corncob has been discussed in this paper. Acid modification of biochar has significantly enhanced decolorization up to 98 %. Speedy removal of color within 45 minutes on using acid modified corncob biochar (MBC) was observed at ambient temperature. Kinetics suggests that the Lagergren's pseudo‐II order model was the best fit for the chemisorption.